Lateral sloshing in partially filled elliptical tanker trucks using a trammel pendulum. (18th March 2009) - Salem, M.I.; Mucino, V.H.; Saunders, E.; Gautam, M.; , A. Lozano-Guzman
Fluid sloshing in partially filled tanker trucks is the problem herein being addressed. In these vehicles, lateral fluid sloshing during turning and sudden lane change manoeuvres is the main cause for low rollover threshold. Fluid models and equivalent mechanical spring-bob and pendulums models have been used to simulate the lateral fluid sloshing in various tank shapes. A novel idea of an elliptical trammel pendulum for elliptical tank geometries is proposed. The bases of selecting the parameters of this pendulum such as pendulum mass, length of arms, and location of fixed mass are derived and verified using a finite element approach.